PENERAPAN PENDEKATAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PADA MATERI LINGKARAN DI KELAS VIII SMP YAYASAN PENDIDIKAN ISLAM DELI TUA T.A 2016/2017 - Fibri Rakhmawati (State Islamic University of North Sumatra, 2017)
The purpose of this research is to know: (1) mathematical communication ability of students in class VIII SMP Yayasan Pendidikan Islam Deli Tua before applied realistic mathematics approach, (2) process of realistic mathematical approach implementation to improve students' mathematical communication ability in circle material in class VIII SMP Yayasan Islamic Education Deli Tua, (3) improvement of students' mathematical communication ability in class VIII SMP Yayasan Pendidikan Islam Deli Tua after applied realistic mathematics approach. This type of research is a classroom action research. The subjects of this study are the students of class VIII-2 SMP Yayasan Pendidikan Islam Deli Tua which amounts to 24 students and the object of this research is the application of realistic mathematical approach to improve students' mathematical communication skills in the circle material in class VIII SMP Yayasan Pendidikan Islam Deli Tua TA 2016/2017 . Data analysis shows that in learning by applying realistic mathematical approach can improve students' mathematical communication ability. The percentage of students' mathematical communication ability level is classified as an improvement in the initial test of 29.17%, in the first cycle of 66.67%, and in cycle II increased to 87.50%. Observations on the process of applying a realistic mathematical approach done by teachers also increased, the result of observation in cycle I is 2.7 which means good and in cycle II is 3.1 which means good. This shows that the application of realistic mathematical approach can improve students' mathematical communication ability in learning mathematics in class VIII SMP Yayasan Pendidikan Islam Deli Tua T.A 2016/2017.